Effect of epicardial fat and metabolic syndrome on reverse atrial remodeling after ablation for atrial fibrillation. Issue 6 (13th October 2018) - Monno, Koyuru; Okumura, Yasuo; Saito, Yuki; Aizawa, Yoshihiro; Nagashima, Koichi; Arai, Masaru; Watanabe, Ryuta; Wakamatsu, Yuji; Otsuka, Naoto; Yoda, Shunichi; Hiro, Takafumi; Watanabe, Ichiro; et al.
Abstract: Background: Metabolic syndrome/epicardial adipose tissue (EAT) plays an important role in atrial fibrillation (AF). Although reverse atrial remodeling (RAR) often occurs after AF ablation, the effects of EAT on RAR remain unknown. Methods: Study subjects were 104 patients in whom transthoracic echocardiography (TTE) was performed before AF ablation and 3, 6, and 12 months afterward. EAT was assessed in terms of its thickness adjacent to the right ventricular anterior wall in the TTE parasternal view. RAR was defined as >10% reduction in the left atrial volume (LAV) index by the 3‐month follow‐up examination. Results: Postablation RAR occurred in 57/104 (55%) patients. RAR absence was associated with a relatively thick EAT (4.92 ± 1.65 vs. 3.92 ± 1.17 mm, P = 0.0005), small LAV index (24.6 ± 7.5 vs. 28.8 ± 10.6 mL/m 2, P = 0.0233), and metabolic syndrome (62% vs. 28%, P = 0.0006). Metabolic syndrome and EAT were shown to be independent predictors of RAR absence. Thick EAT was significantly associated with AF recurrence after ablation (5.05 ± 2.19 mm vs. 4.17 ± 1.16 mm for no AF recurrence group, P = 0.0116), but metabolic syndrome was not (48% vs. 42%, P = 0.6189). Despite no change in body weight, EAT thickness decreased significantly by 12 months in patients without AF recurrence (4.17 ± 1.16 vs. 3.65 ± 1.16 mm, P < 0.0001). Conclusions: EAT and metabolic syndrome appear to be strongly associated with RAR absence, but only the thick EAT was significantly associated with the postablation AF recurrence. Our findings, especially the thinning of EAT, suggest that thick EAT lead to AF vulnerability but that EAT reduction favorably affects ablation outcome.